Começar de novo: políticas de amparo ao trabalhador preso e os desafios à reintegração social - Pereira, Julio Cesar da Silva (Universidade do Vale do Rio dos Sinos, 2021)
The objective of this dissertation is to demonstrate the importance of inclusive policies under perspective of the reintegrating function that the deprivation of liberty must pursue, in view of the return to the post-prison labor market. The process of resocialization of prisoners in the current brazilian scene has been a challenge for the penitentiary system. The problems stem from the lack of infrastructure in prisons across the country, totally out of step with the growing prison population, and also from the inefficiency in the process of re-socializing and reintegrating the inmate into post-prison life. Therefore, the bibliographic study was adopted as a research technique, favoring the search for dissertations, theses, scientific articles, journal and book dossiers, all focused on the area of law and public policy, with the adoption of the Law as a priority interest of Criminal Execution (LEP) as an instrument of the rehabilitation process of the convict and guarantee of rights to prisoners. Next, an analysis of normative and regulatory documents that regulate prison work in the country was carried out, in addition to specific programs that have been implemented in the Federal District. The research confirms the understanding that the inmates' access to labor is an important opportunity for a qualified return to the job market after prison. Therefore, the failure of the prison system in the state's commitment to the reintegration of prisoners is attributed to the lack of effective inclusive policies. It is concluded that the LEP is sufficient normative production to guarantee the need for a prison structure that operates in the prisoner's resocialization process. However, the lack of implementation and support mechanisms from the Federal Government to the States, Municipalities and the Federal District do not guarantee that the LEP is observed in its entirety, causing the prison population to have to serve their sentence without the counterpart of the due guarantees of the law.
Keywords: Sistema prisional; Função ressocializadora; Função reintegradora; Apenado; Políticas inclusivas; Prison system; Resocializing function; Reintegration function; Convicted; Inclusive policies; ACCNPQ::Ciências Humanas::Sociologia